Backstepping Nonlinear Control by using Sliding Mode Observer for controlling Blood Suger - Esfanjani, Mina; Safari, Somayeh; Faress, Fardad (Technium BioChemMed, 2021)
Accurate control and stability of vital variables in patients whose natural control system has been undermined for some reasons are essential. One of these fundamental variables is the blood glucose level of a diabetic person. However similar to most artificial control systems associated with the human body, many complexities and uncertainties force us to use advanced control methods. In this paper, by choosing a successfully applied model, nonlinear controller and observer are designed to control blood glucose level. This mathematical model, which is called Bergman minimal model, approximates the dynamic reaction of a diabetic patient’s blood glucose concentration to the insulin injection. These equations are non-normal nonlinear with some uncertainties. The backstepping method is applied to control the system duo to its non-normal equations. In addition, to estimate state variables and uncertainty, a nonlinear observer-based sliding mode theory has been designed. The simulation results prove the proper performance of this method.